RESULTS OF PLASTY OF POSTINFARCTION LEFT VENTRICULAR ANEURYSM PERFORMED ON THE WORKING HEART - D. G. Tarasov; I. I. Chernov; M. L. Gordeev; A. V. Pavlov (Вестник хирургии имени И.И. Грекова)
The results of plasty (124 patients) of postinfarction left ventricurar aneurysm performed on the working heart are presented in this article. It is shown, that the upgrade of existing surgical techniques, which are directed to the creation of the optimal left ventricle shape, could improve the clinical results after plasty of postinfarction left ventricular aneurysm. It’s important to arrange the conditions, which allow avoiding a negative influence on contractility function of the myocardium. The desired conditions could be obtained, if the plasty is performed on the working or fibrillating heart provided that the patient has a consistent aortic valve.